The Queen's Diamond Jubilee Galleries Westminster Abbey - Payne, Matthew (Scala Arts & Heritage Publishers Ltd, 2018)
In summer 2018, The Queen's Diamond Jubilee Galleries will open in the church's medieval triforium, an internal gallery which runs 70 feet above the floor of the Abbey. Entrance to the space, never before opened to the public, will be through a new tower outside Poets' Corner, opposite the Palace of Westminster. This will be the most significant addition to the Abbey since Nicholas Hawksmoor's iconic towers were completed in 1745.0The treasures displayed will reflect the Abbey's rich thousand-year history. The Galleries will also grant magnificent views to Parliament Square and the Palace of Westminster, as well as wonderful vistas across the Abbey, which Betjeman described as "the finest view in Europe". The Galleries mark the final phase of the Abbey's "2020 Vision", which aimed to improve facilities for the Abbey's two million worshippers and visitors.00Permanent exhibition: opening 11.06.2018